On the sustainability of current account deficits: evidence from four ASEAN countries - Baharumshah, Ahmad Zubaidi; Lau, Evan; Fountas, Stilianos (Elsevier, 2003)
This paper examines the sustainability of the current account imbalance for four ASEAN countries (Indonesia, Malaysia, the Philippines, and Thailand) over the 1961–1999 period. To this end, we utilize the intertemporal budget constraint (IBC) model to explain the behavior of the current account in these countries. The analysis is based on various unit root and cointegration procedures including those allowing for a structural break to deal with the major shortcomings of previous studies. The empirical results indicate clearly that for all countries, except Malaysia, current account deficits were not on the long-run steady state in the pre-crisis (1961–1997) era. This leads us to conclude that the current accounts of these countries were unsustainable and did not move towards external-account equilibrium. Moreover, the persistent current account deficits might serve as a leading indicator of financial crises. In contrast, we find strong comovement between inflows and outflows in Indonesia, the Philippines, and Thailand in the period including the post-crisis years, while Malaysia was on an unsustainable path. This is because macroeconomic performance of most of the ASEAN-4 countries has changed dramatically since the onset of the Asian crisis in mid-1997. The evidence suggests that action to prevent large appreciations should have been taken prior to the 1997 crisis.